Unhealthy Lifestyle Among Sufferers Of Gastritis On Young Adult Age - Esra Desyanti Turnip; Maria Yunita Indriarini; Yosi Maria Wijaya (Universitas Muhammadiyah Surakarta, 2023)
GGastritis is generally experienced by young adults caused by unhealthy lifestyle patterns, including diet, sleep patterns, physical activity, and stress. This study aims to identify the description of the lifestyle of young adults with gastritis that includes diet, sleep pattern, physical activity, and stress. This research method used was quantitative with a cross-sectional design, using a lifestyle questionnaire which was distributed using a Google form to 133 students who were selected through total sampling. The results showed that the average age of respondents was 20.9 years and the majority were women. lifestyle profile found, the total healthy lifestyle was 46.6% unhealthy. Lifestyles include diet, sleep patterns, and physical activity indicating nearly the same results by about 51-52% in unhealthy categories. For stress levels, there were 70.7% respondents in the moderate category. The number of male respondents in the category of healthy lifestyles and do not have the same results (12.8%), whereas in women, 33.8% in the unhealthy category. On the male lifestyle profile, unhealthy categories on physical activity, while in women on eating habits. The conclusion of the study for lifestyle among respondents were in the unhealthy category. Young adults with gastritis are recommended to adopt a healthy lifestyle to avoid the complication of gastritis.